Peningkatan Kemampuan Menulis Naskah Drama Berdasarkan Cerpen Dengan Menggunakan Metode Copy The Master Pada Siswa Kelas Xi.11 Sma Negeri 5 Palembang - Revormasi, Sahlan; Salsabil, Rizka; H, Hetilaniar (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to improve the ability to write drama scripts based on short stories using the copy the master method in class XI.11 students at SMA Negeri 5 Palembang, improve learning outcomes in learning Indonesian and increase student activity in writing. The subjects of this study were 28 class XI.11 students of SMA Negeri 5 Palembang, consisting of 14 males and 14 females. The method used was a quantitative descriptive method and a qualitative descriptive method. The techniques used in data collection were observation and test techniques. This study was conducted in two cycles. Each cycle has stages of planning, implementation, observation, and reflection. Based on the results of the study, it can be concluded that the learning process using the copy the master method can improve students' skills in writing drama scripts based on short stories. The average result of writing drama scripts in cycle II was 80.70, which increased by 18.38 from the results of the previous cycle which was only 62.32. Students who met the KKM also increased, in cycle I only 37.5% of students met the KKM while in cycle II students who met the KKM increased to 91.06%. Based on these data, it can be concluded that there was an increase in the learning outcomes of class XI.11 students at SMA Negeri 5 Palembang after implementing learning using the copy the master method in writing drama scripts based on short stories.